Stereotip Penghuni Mess Cendrawasih Kepada Orang Papua - Sudarmika, Dina; Fransiska, Marta (FISIP Universitas Bung Karno, 2024)
Stereotypw is a process of social clarification carried out by some groups towards other groups by simplifying or generalizing signs, either explicitly or implicitly presenting decision values, or assumptions centered on behavior, characteristics or past history. In the process of social interaction at the Mess Cendrawasih, there are very diverse cultural differences between Javanese, Batak, Palembang and Papuan tribes, which results in intercultural communication barriers in the form of stereotypes. The theory used is the uncertainty reduction theory of Charles Berger and Richard Calabrese. This research uses a qualitative approach with interview data collection techniques. The research results found that the social interactions that occurred at the Mess Cendrawasih resulted in positive stereotypes which were manifested in helpful behavior and polite attitudes. Meanwhile negative stereotypes are manifested in high temperamental behavior (cheap easily), drunkards and gamblers. The stereotypes experienced by Papuan people are not categorized as stereotypes on a large scale so that they do not cause discrimination and also do not disturb the harmony of diverse cultures.Keywords: stereotypes, uncertainty reduction theory, intercultural communication